Local Content Requirements Policy in Indonesia’s Power Plant Development - Sitompul, Rislima Febriani; Silalahi, Mesnan; Sumule, Ophirtus; Ragina , Friga Siera (International Journal of Energy Economics and Policy, 2022)
One of the elements that can increase national resilience is the strength of the domestic industrial sector. A proven and reliable electricity supply is very important in supporting the operations of the industrial sector. Accordingly, a reliable electricity supply is an important and strategic element in the realization of national security. To reduce dependency on imported materials, the Government of Indonesia (GOI) has imposed Local Content Requirements (LCR) mechanism in the electricity sector, especially for the major components of power plants, namely steam turbines, and generators. The ambitious electricity infrastructure development program which dominantly relies on the Coal-Fired Power Plant (CFPP) requires reliable electrical components that support upstream industries which face problems if LCR should be applied. The objective of this study is to analyze the opportunity costs of replacing the required import of steam turbines and generators, as well as to provide recommendations on how LCR would be best be applied in Indonesia, despite its controversies to support the economic development of a country. The result of the study shows the total value of opportunity cost that GOI is likely to gain from imported steam turbines and generators cost for CFPP is ranged at USD 2,896,152,000 - 7,362,750,000 throughout 2019-2028.